2018
DOI: 10.1002/aenm.201802207
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Mediated Li2S Electrodeposition: A Critical Manipulator in Lithium–Sulfur Batteries

Abstract: such as silicene [9a] and ionic compounds [10a] were shown to speed up the Li 2 S lateral passivation rate, leading to lower capacities.Solvent has a strong impact on Li 2 S deposition. The kinetics and morphology of Li 2 S deposition in glyme-based polysulfide solutions was studied and a progressive nucleation and a 2D island growth model was proposed. [6a] In addition, the use of discharge mediator was reported to slow down the impingement of insulating Li 2 S islands on carbon and transform the 2D growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
250
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(261 citation statements)
references
References 57 publications
10
250
0
1
Order By: Relevance
“…As seen in Table , DMC has a low dielectric constant ( ϵ =3.1), which is comparable to that of DEC ( ϵ =2.8); while the dielectric constant of EC is as high as 95.3, with a big donor number of 16 . This may be similar to observations in Li−S system by others, where the dissolution of polysulfides can be significantly suppressed with solvents with low dielectric constant and low donor number . Further work is needed to understand the effect of electrolyte on battery stability.…”
Section: Resultssupporting
confidence: 69%
“…As seen in Table , DMC has a low dielectric constant ( ϵ =3.1), which is comparable to that of DEC ( ϵ =2.8); while the dielectric constant of EC is as high as 95.3, with a big donor number of 16 . This may be similar to observations in Li−S system by others, where the dissolution of polysulfides can be significantly suppressed with solvents with low dielectric constant and low donor number . Further work is needed to understand the effect of electrolyte on battery stability.…”
Section: Resultssupporting
confidence: 69%
“…A structure-property relationship of the solvents revealed that high-DN, high-e, and low-viscosity electrolyte offers the possibility of achieving such a demanding engineering condition. [98] Similar to the solvent in electrolyte, the properties of salt also have effects on the solubility of polysulfides. Since the Li salt and LiPSs possess the same cation Li + , the concentration of the former has a significant effect on the dissolution of the latter.…”
Section: Electrolyte Engineering To Improve Polysulfide Dissolutionmentioning
confidence: 99%
“…The nucleation and growth of Li 2 S 1/2 are intimately affected by current density, deposit-substrate affinity, and intrinsic nucleation sites on substrates. [59][60][61][62][63][64] The atomic Co-N-C electrocatalysts favor Li 2 S 1/2 nucleation through lithium bonds and sulfiphilic sites. 55 The high electrocatalytic property toward LiPS conversion endows the current density peak of the Co-N-C based cell with 1650 s ahead in comparison with C based cell ( Figure 2B).…”
Section: Introductionmentioning
confidence: 99%